Two Mifepristone Doses and Two Intervals of Misoprostol Administration for Termination of Early Pregnancy : A Randomised Factorial Controlled Equivalence Trial - von Hertzen, H. (2012)
OBJECTIVE: To compare the efficacy of 100 mg and 200 mg of mifepristone and 24- and 48-hour intervals to administration of 800 microg vaginal misoprostol for termination of early pregnancy. DESIGN: Placebo-controlled, randomized, equivalence trial, stratified by centre. SETTING: 13 departments of obstetrics and gynecology in nine countries. POPULATION: 2,181 women with 63 days or less gestation requesting medical abortion. METHODS: Two-sided 95% CI for the risk differences of failure to complete abortion were calculated and compared with 5% equivalence margin between two doses of mifepristone and two intervals to misoprostol administration. Proportions of women with adverse effects were compared between the regimens using standard testes for proportions. OUTCOME MEASURES: Rates of complete abortion without surgical intervention and adverse effects associated with the regimens. RESULTS: Efficacy outcome was analysed for 2,126 women (97.5%) excluding 55 lost to follow up. Both mifepristone doses were found to be similar in efficacy. The rate of complete abortion was 92.0% for women assigned 100 mg of mifepristone and 93.2% for women assigned 200 mg of mifepristone (difference 1.2%, 95% CI: -1.0 to 3.5). Equivalence was also evident for the two intervals of administration: the rate of complete abortion was 93.5% for 24-hour interval and 91.7% for the 48-hour interval (difference -1.8%, 95% CI: -4.0 to 0.5). Interaction between doses and interval to misoprostol administration was not significant (P = 0.92). Adverse effects related to treatments did not differ between the groups. CONCLUSIONS: Both the 100 and 200 mg doses of mifepristone and the 24- and 48-hour intervals have a similar efficacy to achieve complete abortion in early pregnancy when mifepristone is followed by 800 micrograms of vaginally administered misoprostol.